2010
DOI: 10.3742/opem.2010.10.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Seed extracts of a Bangladeshi medicinal plant Abrus precatorius L. show antifertility activity in female rats

Abstract: SUMMARYThe seed powder of Abrus precatorius L. has traditionally been used as oral contraceptive agent by the women in some rural areas in Bangladesh. The present study aimed to examine the antifertility activity of A. precatorius seed extracts in experimental female rats. Finely ground seeds were extracted with aqueous acetone followed by successive partitioning with n-hexane, ethyl acetate (EtOAc), methanol (MeOH) and water. Water suspended crude seed powder, organic fractions of acetone extract and a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The results of the Hormonal Pro le study show the APS administrations in female rats showed a decrease in serum concentrations of FSH, LH, Prolactin and Estradiol and a decrease in progesterone in rats receiving APS compared to control, which showed a signi cant decrease in FSH, LH and estradiol levels caused a decrease and the number of developing follicles and increased the number of atretic follicles in the ovary [22]. Prolactin levels were signi cantly increased in the APS administrations compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the Hormonal Pro le study show the APS administrations in female rats showed a decrease in serum concentrations of FSH, LH, Prolactin and Estradiol and a decrease in progesterone in rats receiving APS compared to control, which showed a signi cant decrease in FSH, LH and estradiol levels caused a decrease and the number of developing follicles and increased the number of atretic follicles in the ovary [22]. Prolactin levels were signi cantly increased in the APS administrations compared to the control group.…”
Section: Discussionmentioning
confidence: 97%